With or against the trend - Short-term momentum and contrarian strategies : Quantitative study from the Finnish stock market - Nykänen, Justus (My University, 2025)
Momentum and contrarian anomalies have been increasingly examined, especially since De Bondt and Thaler’s (1985) and Jegadeesh and Titman’s (1993) studies. Momentum and contrarian studies utilize technical analysis to identify specific recurring patterns based on historical data. The short-term return continuity and long-term return reversal of winner and loser stocks have been recognized as one of the strongest market anomalies, existing across industries, firm characteristics, different asset classes, and various geographical regions (Rouwenhorst, 1998; Moskowitz & Grinblatt, 1999; Lewellen, 2002; Moskowitz et al., 2012). According to Fama's (1970) efficient market hypothesis, all information is already reflected in stock prices, and historical data cannot be used to predict future prices. Under the efficient market hypothesis, the efficient market will adjust if any irrationality occurs, ensuring that such inefficiencies eventually disappear in the long run. Momentum and contrarian appear to be exceptions, as they still exist despite drawing significant attention. This thesis examines the continuation and reversal of returns in the short term within the Finnish stock market from 2009 to 2022. This thesis also seeks to compare the effectiveness of various investment strategies against one another and against the average index return to ascertain their potential for generating excess returns. This thesis tests the performance of four strategies that vary in terms of historical lag, i.e., the period of cumulative returns over which stocks are ranked. All strategies use a uniform holding period of one month, with portfolios rebalanced monthly. The strategies examined include standard momentum, recent past performance, intermediate past performance, and past performance over a single month. This study uses historical stock price data from 81 stocks that have maintained their listing on Nasdaq Helsinki throughout this period. The findings of this study reveal that short-term continuation and reversal of returns are present in the Finnish stock market. Continuity of returns is evident in the 2 to 12 months before portfolio formation, during which winner stocks outperform loser stocks on average. In contrast, the only instance where loser stocks outperform winner stocks occurs in the short-term reversal strategy (the t-1 lag) and in the t-13 strategy, where loser stocks rebound significantly, outperforming the winner stocks. The most effective strategy identified in this analysis is the standard momentum strategy, which produces an average monthly return of 1.59% and a significant t-statistic of 2.81 at a 5% significance level. Overall, five of the thirteen zero-cost momentum portfolios demonstrate the ability to outperform the average market return, while two contrarian portfolios achieve this as well. It is important to note that this study does not consider transaction costs. Therefore, the practical implementation of these strategies may not necessarily guarantee excess returns.

Momentum- ja contrarian anomalioita on tutkittu yhä enemmän erityisesti De Bondtin ja Thalerin (1985) sekä Jegadeeshin ja Titmanin (1993) tutkimusten jälkeen. Momentum- ja contrarian-tutkimuksissa käytetään teknistä analyysia erityisten toistuvien mallien tunnistamiseksi historiatietojen perusteella. Voittaja- ja häviäjäosakkeiden lyhyen aikavälin tuottojen jatkuvuus ja pitkän aikavälin tuottojen käänteisyys on tunnustettu yhdeksi vahvimmista markkina-anomalioista, joita esiintyy eri toimialoilla, yritysten ominaisuuksissa, eri omaisuusluokissa ja eri maantieteellisillä alueilla (Rouwenhorst, 1998; Moskowitz & Grinblatt, 1999; Lewellen, 2002; Moskowitz et al., 2012). Faman (1970) tehokkaiden markkinoiden hypoteesin mukaan kaikki informaatio on jo heijastunut osakkeiden hintoihin, eikä historiatietoja voida käyttää tulevien hintojen ennustamiseen. Tehokkaiden markkinoiden hypoteesin mukaan tehokkaat markkinat sopeutuvat, jos epärationaalisuutta esiintyy ja varmistavat, että tällainen tehottomuus lopulta häviää pitkällä aikavälillä. Momentum- ja contrarian-anomaliat näyttävät olevan poikkeuksia, sillä ne ovat edelleen olemassa vaikka ovat saaneet paljon huomiota. Tässä tutkielmassa tarkastellaan tuottojen jatkumista ja kääntymistä lyhyellä aikavälillä Suomen osakemarkkinoilla vuosina 2009-2022. Tutkielmassa pyritään myös vertailemaan eri sijoitusstrategioiden tehokkuutta toisiinsa ja indeksin keskimääräiseen tuottoon nähden, jotta voidaan selvittää niiden mahdollisuudet ylituottojen tuottamiseen. Tässä tutkielmassa testataan neljän strategian tehokkuutta, jotka eroavat toisistaan historiallisen viiveen eli kumulatiivisten tuottojen jakson suhteen, jonka aikana osakkeet asetetaan paremmuusjärjestykseen. Kaikissa strategioissa käytetään yhden kuukauden pitoaikaa, ja salkut tasapainotetaan kuukausittain. Tutkittuihin strategioihin kuuluvat standardimomentum, viimeaikainen aiempi kehitys, keskivaiheen aiempi kehitys ja yhden kuukauden aiempi kehitys. Tässä tutkimuksessa käytetään historiallisia kurssitietoja 81 osakkeesta, jotka ovat säilyttäneet listautumisensa Nasdaq Helsinkiin koko tämän ajanjakson ajan. Tämän tutkimuksen tulokset osoittavat, että Suomen osakemarkkinoilla esiintyy lyhyen aikavälin tuottojen jatkumista ja kääntymistä. Tuottojen jatkuvuus on ilmeistä salkunmuodostusta edeltävien 2-12 kuukauden aikana, jolloin voittajaosakkeet tuottavat keskimäärin paremmin kuin häviäjäosakkeet. Sitä vastoin ainoa tapaus, jossa häviäjäosakkeet tuottavat voittajaosakkeita paremmin, esiintyy lyhyen aikavälin käänteisstrategiassa (t-1-viive) ja t-13-strategiassa, jossa häviäjäosakkeet elpyvät merkittävästi ja tuottavat voittajaosakkeita paremmin. Tehokkain tässä analyysissä tunnistettu strategia on standardimomentumstrategia, jonka keskimääräinen kuukausituotto on 1,59% ja jonka t-statistiikka on 2,81 5% merkitsevyystasolla. Kaiken kaikkiaan viisi kolmestatoista nollakustannus momentum-salkusta osoittaa kykenevänsä tuottamaan keskimääräistä markkinatuottoa paremmin, kun taas kaksi contrarian-salkkua saavuttaa tämän myös. On tärkeää huomata, että tässä tutkimuksessa ei oteta huomioon transaktiokustannuksia. Siksi näiden strategioiden käytännön toteutus ei välttämättä takaa ylituottoja.
Keywords: strategies; investments; financial markets; anomaliat; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance